2021
DOI: 10.1007/s00228-021-03232-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cannabichromene in a medical cannabis product also containing cannabidiol and Δ9-tetrahydrocannabinol: a pilot study

Abstract: Purpose Cannabichromene (CBC) is a phytocannabinoid commonly found in cannabis, yet its acute post-dose pharmacokinetics (PK) have not been examined in humans. This is a secondary data analysis from a trial investigating Spectrum Yellow oil, an oral cannabis product used for medical purposes that contained 20 mg cannabidiol (CBD), 0.9 mg Δ9-tetrahydrocannabinol (THC), and 1.1 mg CBC, per 1 mL of oil. Methods Participants (N = 43) were randomized to one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For example, a recent survey of the U.S. marketplace indicated that the total cannabinoid content in hemp‐derived products ranged from lower than detection limit to 143 mg per serving, with a median of 16.7 mg per serving (Dubrow et al, 2021). In addition, similar oral doses have been administered in the clinical studies for cannabinoids (Hobbs et al, 2020; Peters et al, 2022). Since the hemp‐derived products have been commonly manufactured using formulations such as liquid and capsule, an immediate release suspension (capsule yielded same results) was selected for the PBPK simulations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent survey of the U.S. marketplace indicated that the total cannabinoid content in hemp‐derived products ranged from lower than detection limit to 143 mg per serving, with a median of 16.7 mg per serving (Dubrow et al, 2021). In addition, similar oral doses have been administered in the clinical studies for cannabinoids (Hobbs et al, 2020; Peters et al, 2022). Since the hemp‐derived products have been commonly manufactured using formulations such as liquid and capsule, an immediate release suspension (capsule yielded same results) was selected for the PBPK simulations.…”
Section: Discussionmentioning
confidence: 99%
“…All solvents used for UHPLC analyses were HPLC grade and were purchased from Merck Life Science (Milan, Italy) and Carlo Erba Reagents (Milan, Italy). Cannabinoid reference standards dissolved in methanol, namely, cannabidivarin (CBDV, 1 mg/mL), cannabidiolic acid (CBDA, 1 mg/mL), cannabigerol (CBG, 1 mg/mL), cannabidiol (CBD, 1 mg/mL), cannabinol (CBN, 1 mg/mL), (−)-Δ 9 tetrahydrocannabinol [(−)-Δ 9 -THC, 1 mg/mL], (−)-Δ 8 -tetrahydrocannabinol [(−)-Δ 8 -THC, 1 mg/mL], cannabichromene (CBC, 1 mg/mL), and (−)-Δ 9 -tetrahydrocannabinolic acid ((−)-Δ 9 -THCA, 1 mg/mL) with a purity of ≥99%, were purchased from Merck Life Science (Milan, Italy). Preparative TLC plates UV 254 nm (surface 20 × 20 cm, thickness 500 μm), used for the purification of CBC, were purchased from Merck (Darmstadt, Germany).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…4 This synthetic material was used in the bioactivity studies that led to the discovery that CBC is a potent and selective CB2 5 and TRPA1 6 agonist, providing a mechanistic basis for its powerful anti-inflammatory activity, 7 while a remarkable antiepileptic activity was also reported. 8 The observation that CBC has a better oral absorption compared to CBD (2) and Δ 9 -THC (3) 9 provided an additional incentive for clinical studies, which are so far ongoing only with combination products. 9 CBC (1a) is chiral and was originally isolated in 1966 in an optically active form, 10,11 as was its acidic precursor (cannabichromenic acid, CBCA, 1b).…”
mentioning
confidence: 99%
See 2 more Smart Citations